Effect of air pollution on plant life in the city of Chittagong, Bangladesh - Jubaer, Ahmed; Ali, Mohammed Khorshed; Hassan, Saiyed Mahmud Tanvir; Islam, Md.Shahidul; Alam, Muhammad Mahabub; Islam, Sajia; Talukder, Mohammad Zahirul Islam; Sourav, Rubayat Tahrim (European Journal of Chemistry, 2024)
Bangladesh faces a serious problem with air pollution, which has a negative impact on human health and tree health. Leaf damage, slow development, and decreased photosynthetic activity are just a few of the harmful effects on trees that have been linked to high concentrations of pollutants such as particulate matter, sulfur dioxide, and nitrogen oxides. These consequences affect the aesthetic value of green spaces in addition to interfering with the functions of the ecosystem that trees offer, such as air filtration and carbon sequestration. Given the seriousness of the problem, the present study plan was implemented to evaluate the amount of pollutants such as SOx, NOx, O3, hydrocarbons, particulate matter 2.5, particulate matter 10 and suspended particulate matter in the air in several urban areas of Chittagong and to evaluate the amount of chlorophyll from the leaves of affected and without affected leaves so that it may understand how the photosynthesis process of plants is interrupted by air pollution. 2 Number Gate Circle, Akbarsha Lane Circle, Alongkar Mor Bus Stop, Barik Building Circle, BDR Field Circle, Halishahar Access Road, Artillery Center-North Halishahar, Bangladesh Forest Research Institute and CRB Circle were selected as sampling location based on their heavy traffic and crowdedness. For the analysis of chlorophyll, each plant leaves were collected in three sections such as unaffected, slightly affected, and affected for comparison. The data studied showed that the most polluted zone with particulate matter had a lower chlorophyll concentration in the surrounding tree leaves. This can indicate that particulate matter can hinder photosynthesis reactions.